A Compact Circular Polarized MIMO Fabric Antenna with AMC Backing for WBAN Applications - Pathan, T. U.; Kakde, B. (Advanced Electromagnetics, 2022)
A compact high-isolation diversity and circular polarized (CP) multiple-input multiple-output (MIMO) fabric antenna for 2.4 GHz ISM band applications is presented. A metamaterial (MTM)-inspired radiating element is used for the miniaturization of the presented fabric antenna. The proposed antenna is fabricated on a denim substrate and has a dimension of 58 mm x 23 mm x 1.6 mm. The circular polarization is achieved by trimming the two diagonal corners of the radiating elements. A defected ground structure (DGS) comprising two U-slots is placed underneath each radiator to increase the bandwidth of the presented antenna. The isolation characteristics between the two antenna elements are increased by 20 dB by cutting a slit in a ground plane. The proposed CP-MIMO antenna incorporates an artificial magnetic conductor (AMC) layer to limit backward radiation towards the human body and hence enhances the gain. This antenna has been created on a denim substrate with permittivity εr =1.6 and 1.6 mm thickness. The proposed antenna offers a fractional bandwidth of 6.6 % (2.38-2.54 GHz), and an impedance bandwidth about 160 MHz. The antenna has a peak gain of 2.5 dBi without AMC and 4.5 dBi with AMC. To validate the simulation results, a prototype for the proposed antenna has been fabricated and experimentally characterized. Due to its small size, low specific absorption rate (SAR), ease of integration, and robustness, this antenna is a good option for wireless body area network (WBAN) applications.